The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1088/0004-637x/730/2/78
|View full text |Cite
|
Sign up to set email alerts
|

A PANCHROMATIC VIEW OF NGC 602: TIME-RESOLVED STAR FORMATION WITH THEHUBBLEANDSPITZERSPACE TELESCOPES

Abstract: We present the photometric catalogs for the star-forming cluster NGC 602 in the wing of the Small Magellanic Cloud covering a range of wavelengths from optical (HST/ACS F555W, F814W and SMARTS/ANDICAM V, I) to infrared (Spitzer /IRAC 3.6, 4.5, 5.8, and 8 µm and MIPS 24 µm). Combining this with IRSF (InfraRed Survey Facility) near-infrared photometry (J, H, K s ), we compare the young main sequence (MS) and pre-main sequence (PMS) populations prominent in the optical with the current young stellar object (YSO) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(75 citation statements)
references
References 55 publications
(85 reference statements)
3
72
0
Order By: Relevance
“…The YSO model set does not include multiple sources. However, we showed in Carlson et al (2011) that the SED fitter can be used in the identification of YSOs even when they are members of protoclusters. This is in part because we expect one or two sources to dominate the luminosity of a protocluster: L YSO ∝ M each of these factors might contribute to the overall error budget for SED fitting is difficult.…”
Section: Yso Candidate Selection and Classificationmentioning
confidence: 97%
See 2 more Smart Citations
“…The YSO model set does not include multiple sources. However, we showed in Carlson et al (2011) that the SED fitter can be used in the identification of YSOs even when they are members of protoclusters. This is in part because we expect one or two sources to dominate the luminosity of a protocluster: L YSO ∝ M each of these factors might contribute to the overall error budget for SED fitting is difficult.…”
Section: Yso Candidate Selection and Classificationmentioning
confidence: 97%
“…For fitting, we require sources meeting at least 1α criterion to have at least 4 bands of photometry defining the SED and consider a relatively large χ 2 min /pt well-fit (i.e. reduced χ 2 ; see Carlson et al 2011, for a detailed explanation). We consider sources with at least 1α selection criterion and falling within either an α or β selection region in all five CMDs to be the most reliable.…”
Section: Yso Candidate Selection and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…This discovery showed that these MYSOs are not isolated, at least not as far as their immediate environments are concerned. The observational contradiction between high-and low-resolution imaging about the isolation of high-mass stellar sources in the Magellanic Clouds is an issue that is already discussed in the literature (e.g., Gouliermis et al 2007;Carlson et al 2011). Including our dataset, every MYSO resolved with HST is found to be surrounded by lower-mass red sources.…”
Section: Estimates Of Cluster Massesmentioning
confidence: 99%
“…We employed the three-dimensional radiative transfer code HOCHUNK3D for protostars, which was developed by Whitney et al (2013) based on the two-dimensional version (Whitney et al 2003a(Whitney et al , 2003b(Whitney et al , 2004) that has been widely used in previous infrared surveys of protostars (e.g., Young et al 2005;Haisch et al 2006;Bolatto et al 2007;Carlson et al 2007Carlson et al , 2011Chapman et al 2007;Harvey et al 2007;Hatchell et al 2007;Simon et al 2007;Tobin et al 2007;Merín et al 2008;Poulton et al 2008;Seale & Looney 2008;Whitney et al 2008;Enoch et al 2009;Forbrich et al 2010;Gramajo et al 2010;Samal et al 2012;Stutz et al 2013). While HOCHUNK3D is equipped to deal with spiral and warp structures and gaps in the disk, our current study is focused on the two-dimensional structures of protostellar disks and envelopes.…”
Section: Radiative Transfer Modelsmentioning
confidence: 99%